Issues in blues improvising among modern instrumentalists at Faculty of Music Universiti Teknologi Mara / Muhammad Haniff Abd Rahman - Abd Rahman, Muhammad Haniff (Faculty of Music, 2015)
The main aim of this thesis is to study Blues improvisation and their understanding about Blues music itself. The paperwork includes affectiveness of study in music, Pentatonic scale, Blues scale, networking, technical approach on handling music instruments, experience on music and style of improvisations. This study is performed to measure the usage of scales, modes and techniques during Blues improvisations in solo performances among modern instruments students in Universiti Teknologi Mara. To achieve this, data has been collected by research from journal from other researchers, books, online journal and peer's self-thoughts. The paper analyzes the overall factor that happened before and during performances. Through researcher's own experiences during three year studies for Bachelor's Degree in UiTM, the researcher has involved in most modern performances. Most of the time, the musicians facing problems during improvisations in solo part. In researcher's own hypothesis, most of modern instrument students lack of ideas during solo improvisations performances due to social factors, lack of skills and ability to improvise and not mastering scales. Thus, using all the information received, the researcher will design an interview questions based on the issues related to the topic.